BSC2 induces multidrug resistance via contributing to the formation of biofilm in Saccharomyces cerevisiae. (13th September 2021) - Huang, Zhiwei; Dai, Hongsheng; Zhang, Xiaoyu; Wang, Qiao; Sun, Jing; Deng, Yunxia; Shi, Ping
Abstract: Biofilm plays an important role in fungal multidrug resistance (MDR). Our previous studies showed that BSC2 is involved in resistance to amphotericin B (AMB) through antioxidation in Saccharomyces cerevisiae . In this study, the overexpression of BSC2 and IRC23 induced strong MDR in S. cerevisiae . BSC2 ‐overexpression affected cellular flocculation, cell surface hydrophobicity, biofilm formation and invasive growth. However, it failed to induce caspofungin (CAS) resistance and affect the invasive growth in FLO mutant strains ( FLO11 Δ, FLO1 Δ, FLO8 Δ and TUP1 Δ). Furthermore, the overexpression of BSC2 compensated for chitin synthesis defects to maintain the cell wall integrity and significantly reduced the cell morphology abnormality induced by CAS. However, it could not repair the cell wall damage caused by CAS in the FLO mutant strains. Although BSC2 overexpression increased the level of mannose in the cell wall, DPM1 overexpression in both BY4741 and bsc2 ∆ could confer resistance to CAS and AMB. In addition, BSC2 overexpression significantly increased the mRNA expression of FLO11, FLO1, FLO8 and TUP1 . BSC2 may function as a regulator of FLO genes and be involved in cell wall integrity in yeast. Taken together, our data demonstrate that BSC2 induces MDR in a FLO pathway‐dependent manner via contributing to the formation of biofilms in S. cerevisiae . Take Aways: Overexpression of BSC2 induced strong MDR in S. cerevisiae . BSC2 affected cellular flocculation, CSH, biofilm formation and invasive growth. BSC2 could not repair the cell wall damage caused by CAS in the FLO mutants. BSC2 may function as a regulator of FLO genes to maintain cell wall integrity. BSC2 promotes biofilm formation in a FLO pathway‐dependent manner to induce MDR. Abstract : BSC2 promotes biofilm formation in a FLO pathway‐dependent manner to induce MDR.